Interorganizational Logistics Entities: Categorization of Forms and Quantitative Evaluation - Aleksandr V. Parfenov, Natalia A. Gviliya,; Shulzhenko, Tatiana G. (Opción, 2019)
The paper explores and categorizes interorganizational logistics entities. Based on the expert survey data and the analysis of aggregate indicators of the intersystem logistics entities, the most integrated intersystem logistics entities were identified. The results indicate that the most integrated intersystem logistics entities in the Russian Federation are integrated corporate-level logistics systems and strategic alliances. In conclusion, when the level of interorganizational logistics integration was used as a measurement, the most significant relationships turned out to be the ones between strategically integrated corporations — strategic alliances and intercorporate logistical systems.